Effects of biochar on the growth of maize in coastal salt-affected soil in the Yellow River Delta - Zhao Lumeng; Chen Kun; Wang Tianwen; Zhao Lize; Liang Zhimeng (E3S Web of Conferences)
Global climate change is exerting profound impacts on coastal ecosystems in the Yellow River Delta, leading to significant degradation, with plant growth constrained by dual stressors of saltwater intrusion and declining nutrient supply. To investigate the effects of biochar (BC) on maize growth in coastal salt-affected soil of the Yellow River Delta, this study employed a pot experiment to systematically analyze the impact of maize straw BC (pyrolyzed at 300 °C, 450 °C, and 600 °C) on maize growth in coastal salt-affected soil. The results demonstrated that BC treatments at different pyrolysis temperatures significantly increased the net photosynthetic rate (232.40%–379.72%), stomatal conductance (87.47%–244.24%), and transpiration rate (69.52%–219.05%) of maize, thereby promoting biomass accumulation. Specifically, the root fresh weight in the BC300 and BC450 treatment groups increased by 211.29% and 162.44%, respectively, compared to CK, significantly higher than that of BC600 (104.84%). This study confirms that BC amendment can effectively improve photosynthetic performance and biomass accumulation in maize grown in salt-affected soil, with medium-low temperature BC exhibiting superior effects. These findings provide a theoretical basis for salt-affected soil remediation, maize productivity enhancement, and ecological restoration with carbon sequestration potential in coastal wetlands.